ICAR-Central Institute for Subtropical Horticulture, Rehmankhera, Lucknow, Uttar Pradesh 226 101, India - Adak, Tarun; Kumar, Kailash; Shukla, S K; Pandey, G (The Indian Journal of Agricultural Sciences, 2020)
Improvement of sustainable yield index (SYI) in fruit crop is the most important aspect of orchard sustainability and economic enhancement of fruit growers for which an investigation was laid out to improve SYI in guava (Psidium guajava L.) cv Shewta under different integrated nutrient management systems. Higher SYI was obtained using organic + inorganic systems (0.66) followed by NPK fertilization in soil (0.67) or foliar application of micronutrients (0.71) as compared to control (0.45) or adoption of sole organic sources of nutrition (0.45). A range of variation in SYI from 0.44 to 0.77 was recorded across treatments and seasons. The Reference ET0 and pan evaporation was varied between 0.82 to 5.33 mm/day and 1.30 to 7.0 mm/day respectively during reproductive stages of guava. Changes in soil physical properties were recorded across three depths (0-10, 10-20 and 20-30 cm); water holding capacity and porosity varied across the depths and treatments; 19.53 to 24.48% and 39.92 to 50.20 % respectively. Improvement in these two parameters might have contributed towards better SYI in guava. The co-efficient of variation (CV%) of guava productivity based on yield stability indicated lower the variation (1.2 to 4.9) higher is the stability. The dynamic variations in total fruit yield 31.4 to 72.5 kg/tree indicated immediate need for precise soil management to enhance yield potentiality. Conclusively for better SYI in guava, the nutrient requirement through organic (FYM, Azotobacter, PSM, organic mulching Trichoderma etc.) and inorganic (NPK, micronutrients) sources are essentially required in soils of inherently low or poor fertility status.